2013
DOI: 10.1111/resp.12005
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐sectional epidemiological survey of asthma in Jinan, China

Abstract: The asthma prevalence for all ages in Jinan was relatively low compared with that in western countries; however, local asthma control fell markedly short from the goals of the Global Initiative for Asthma (GINA) criteria for asthma management, which may be attributed to the poor adherence to GINA guidelines, especially the underuse of preventative medication of inhaled corticosteroids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 34 publications
1
24
0
1
Order By: Relevance
“…The reported asthma cases accounted for 3.4% of our study population, which was higher prevalent than that previously reported in Jinan districts, China (sample aged 0–14 years, 0.7%) [38]. In addition, this study identified a relatively high prevalence of habitual snoring as well (12.2%), compared to 10.9% in Hong Kong children aged 6–12 years [28], 10.0% in French children aged 5 to 6 years [12], and 11.4% in British children aged 4 to 7 years [39].…”
Section: Discussionmentioning
confidence: 55%
“…The reported asthma cases accounted for 3.4% of our study population, which was higher prevalent than that previously reported in Jinan districts, China (sample aged 0–14 years, 0.7%) [38]. In addition, this study identified a relatively high prevalence of habitual snoring as well (12.2%), compared to 10.9% in Hong Kong children aged 6–12 years [28], 10.0% in French children aged 5 to 6 years [12], and 11.4% in British children aged 4 to 7 years [39].…”
Section: Discussionmentioning
confidence: 55%
“…In two different local population surveys in Korea, current asthma (defined by current wheeze and positive airway hyperresponsiveness) was consistently more prevalent among the elderly (12.7-15.3%) [20, 21]. These age-related increase were similarly observed in several questionnaire-based studies from China [15, 17], Taiwan [37], Mongolia [22], Korea [38], Iran [25], India [8, 11, 28, 31], and Bangladesh [32, 39]. In Japanese nationwide surveys using questionnaires, only wheeze but not physician diagnosed asthma increased with aging [10].…”
Section: How Prevalent Is Adult Asthma In Asia?mentioning
confidence: 67%
“…Specifically, local area prevalence in China was reported as 0.7-3.8% [15, 16, 17, 18, 19]. In two Korean local area studies, current asthma prevalence was 3.6-5.8% when defined by combination of questionnaire and methacholine challenge tests [20, 21].…”
Section: How Prevalent Is Adult Asthma In Asia?mentioning
confidence: 99%
See 1 more Smart Citation
“…Among 59 935 respondents to the China National Health and Wellness Surveys conducted between 2010 and 2013, 1.99% reported a diagnosis of asthma, with 77.0% considered to have mild asthma based on GINA guidelines . A cross‐sectional survey of 13 645 individuals residing in Jinan, China, revealed that poor asthma control was attributed to suboptimal adherence to the GINA treatment guidelines and underutilization of ICS …”
Section: Introductionmentioning
confidence: 99%